2020
DOI: 10.3390/ani10050866
|View full text |Cite
|
Sign up to set email alerts
|

Sound Analysis to Predict the Growth of Turkeys

Abstract: Protocols for manual weighing of turkeys are not practical on turkey farms because of the large body sizes, heavy weights and flighty nature of turkeys. The sounds turkeys make may be a proxy for bird weights, but the relationship between turkey sounds and bird weights has not been studied. The aim of this study was to correlate peak frequency (PF) of vocalization with the age and weight of the bird and examine the possibility using PF to predict the weight of turkeys. The study consisted of four trials in Egy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Lee et al [ 34 ] use more acoustic parameters to automatically detect stress in laying hens. Abdel-Kafy et al [ 35 ] found a highly significant negative correlation between the peak frequency of vocalisations and the weight and age of turkeys. Du et al [ 36 ] also address stress in laying hens by means of their vocalisation analysis, with the final goal of assessing their thermal comfort condition.…”
Section: Related Workmentioning
confidence: 99%
“…Lee et al [ 34 ] use more acoustic parameters to automatically detect stress in laying hens. Abdel-Kafy et al [ 35 ] found a highly significant negative correlation between the peak frequency of vocalisations and the weight and age of turkeys. Du et al [ 36 ] also address stress in laying hens by means of their vocalisation analysis, with the final goal of assessing their thermal comfort condition.…”
Section: Related Workmentioning
confidence: 99%
“…Microphones installed in the farm environment can capture and discriminate vocalisations from many animals simultaneously, making them a powerful tool for monitoring affective state. Vocalisations have been demonstrated to convey information about affective states in a wide range of farm animals [8,71,72], including pigs [73], cows [74] and chickens [75]. Vocalizations are often involuntary, especially those indicating negative affective states, and so are good indicators of immediate emotional reactions in animals [9].…”
Section: Microphones-vocalisationsmentioning
confidence: 99%
“…However, these models need to be updated, compared to genetic lines, and be applied to heat stress situations. New approaches are being used to predict growth such as the statistical analysis of turkeys' grunt sounds to predict growth ( Abdel-Kafy et al., 2020 ). These types of data sets can be valuable in the future to build prediction models or growth curves.…”
Section: Discussionmentioning
confidence: 99%